2008
DOI: 10.1021/ja8045519
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Directing Group Ability in Palladium-Catalyzed C−H Bond Functionalization

Abstract: This paper describes a detailed investigation of factors controlling the dominance of a directing group in Pd-catalyzed ligand-directed arene acetoxylation. Mechanistic studies, involving reaction kinetics, Hammett analysis, kinetic isotope effect experiments, and the kinetic order in various reagents, have been conducted for a series of different substrates. Initial rates studies of substrates bearing different directing groups showed that these transformations are accelerated by the use of electron withdrawi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
176
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(182 citation statements)
references
References 82 publications
4
176
0
2
Order By: Relevance
“…A similar study on relative directing group ability at palladium also concluded that the C À H activation step did not correspond to the overall selectivity in some palladium-catalysed CÀH activation reactions. [31] 2 A C H T U N G T R E N N U N G (p-cymene)} 2 ] cyclometallation is less thermodynamically favourable, hence fewer ligands cyclometallate. The ligands can be divided into three categories, those that cyclometallate with all three metals (pyridine, pyrazole, alkyl imine), those that work well with Ir but fail with either Rh or Ru (aryl imine, oxazoline), and those that under these conditions only work with Ir (oxime, triazole, imidazole, amine).…”
Section: Discussionmentioning
confidence: 99%
“…A similar study on relative directing group ability at palladium also concluded that the C À H activation step did not correspond to the overall selectivity in some palladium-catalysed CÀH activation reactions. [31] 2 A C H T U N G T R E N N U N G (p-cymene)} 2 ] cyclometallation is less thermodynamically favourable, hence fewer ligands cyclometallate. The ligands can be divided into three categories, those that cyclometallate with all three metals (pyridine, pyrazole, alkyl imine), those that work well with Ir but fail with either Rh or Ru (aryl imine, oxazoline), and those that under these conditions only work with Ir (oxime, triazole, imidazole, amine).…”
Section: Discussionmentioning
confidence: 99%
“…[21] With the oxidant iodosobenzene diacetate, PhI(OAc) 2 , the corresponding acetoxylation product is formed in acetonitrile, whereas selective alkoxylation reactions are possible in alcoholic solvents. The CÀH functionalization of single arenes proceeds with high selectivity [22] for the ortho position; thus, this reaction provides unprecedented access to higher functionalized aromatic compounds, such as 2-acetoxyazobenzene (Scheme 5 b). Replacement of the oxidant PhI(OAc) 2 with a combination of Oxone and acetic acid gave a system of comparable efficiency for the ortho acetoxylation of acetophenone and aniline derivatives (Scheme 5 c,d).…”
Section: Cào and Càx Bond Formationmentioning
confidence: 99%
“…have been deployed for the C H activation reactions. The aldehyde C H activation by direct acylation of aryl halides with aliphatic aldehydes is an interesting prospect to get alkyl-aryl ketones; which are potential intermediates in different pharmaceutical, fragrance, dye and agrochemical industries [14][15][16][17][18][19][20][21][22]. Friedel-Crafts acylation has been a traditional way of acylating arenes, which has the strict limitation of reacting with activated benzene derivatives only [23].…”
Section: Introductionmentioning
confidence: 99%